The Influence Of Hedonic Shopping Motivation, Shopping Lifestyle And Packaging Design On Impulse Buying Consumers Of Oh! Some Products In Palu City - Syaban Nur; Syamsul Bahri Dg Parani; Zakiyah Zahara; Asriadi Asriadi (UNIVED Press, 2026)
This study examines the influence of Hedonic Shopping Motivation, Shopping Lifestyle, and Packaging Design on impulse buying behavior of Oh! Some consumers in Palu, using 130 respondents and multiple linear regression analysis with SPSS. The results show that Shopping Lifestyle and Packaging Design have a significant effect on impulse buying, while Hedonic Shopping Motivation does not. These findings indicate that shopping habits and packaging appeal play a greater role in driving impulse purchases than hedonic motivation. Consumers are more triggered by lifestyle patterns and product visuals when making spontaneous buying decisions.